Depression has an impact on disease activity and health‐related quality of life in rheumatoid arthritis: A systematic review and meta‐analysis. (19th December 2019) - Zhang, Lijuan; Cai, Pingping; Zhu, Weiyi
Abstract: Objective: The aim of this study was to explore the impact of depression on pain, disease activity, functional disability and quality of life in patients with rheumatoid arthritis (RA). Methods: English (PubMed, the Cochrane Library, Web of Science and PsycINFO) and Chinese (Wan Fang Database and Chinese National Knowledge Infrastructure) databases were systematically and independently searched from their inception until 30 September, 2019. Studies evaluating the impact of depression on pain, disease activity, functional disability and quality of life with the use of the Short Form‐36 questionnaire (SF‐36) scoring system were included. Statistical analyses were performed with Revman5.3. Data were pooled using a fixed or random‐effects model according to heterogeneity. Results: A total of 7 identified studies matched the inclusion criteria, reporting on a total of 1078 patients with RA in the analysis. The total Disease Activity Score in 28 joints was significantly higher in patients with depression than in patients without depression [standardized mean difference (SMD) =0.47, 95% CI 0.10‐0.85, P  = .01]. All SF‐36 dimensions (physical function, role physical function, emotional role function, vitality, mental health, social function, body pain, general health, physical component scale, mental component scale) were lower in patients with depression than in groups without depression. Interestingly, the results of this meta‐analysis showed no significant difference between patients with and without depression in pain (SMD = 0.57, 95% CI − 0.03‐1.17, P  = .06) and functional disability (SMD = 0.48, 95% CI − 0.03‐0.99, P  = .43). Conclusion: This meta‐analysis showed that RA patients with depression tended to have higher disease activity and lower quality of life than patients without depression.